A descriptive study of the akinosi technique of mandibular nerve block as an alternative to the classical inferior alveolar nerve block - Aguilar, Christine Miriam T.
The purpose of this study as to verify whether the Akinosi technique is a viable alternative to conventional technique for mandibular anesthesia for the extraction of teeth. Forty subjects, ages ranging from 20-35 years old with no systemic disease, were selected from the walk-in patients of the UP-PGH OPD Department of Dentistry, Oral Surgery Service. All subjects were indicated for extractions of mandibular teeth. Twenty subjects were anesthetized using the Akinosi technique and the other twenty, the conventional technique. Each method was evaluated based on the presence of pain during injection, profoundness of anesthesia, need for supplementary injections and operator acceptability. It was founf that this method of anesthesia is painless, less profound but more acceptable to the operators due to its ease of administration. Based on these findings, it was concluded that the conventional technique remains to be the method of choice for anesthetizing mandibular teeth because of its profundity. However, the advantages of the Akinosi technique, such as ease in learning, simplicity of administration, usefulness in cases of infection and limited jaw opening make this method a viable alternative to the conventional technique.